2016
DOI: 10.1016/j.antiviral.2016.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a host-targeted antiviral that abrogates herpes simplex virus replication through modulation of arginine-associated metabolic pathways

Abstract: Since their inception five decades ago, most antivirals have been engineered to disrupt a single viral protein or process that is essential for viral replication. This approach has limited the overall therapeutic effectiveness and applicability of current antivirals due to restricted viral specificity, a propensity for development of drug resistance, and an inability to control deleterious host-mediated inflammation. As obligate intracellular parasites, viruses are reliant on host metabolism and macromolecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 68 publications
1
27
0
2
Order By: Relevance
“…L-Arginine also serves as an essential role in viral replication. Herpes simplex viruses (HSV-1 and HSV-2), varicella-zoster virus (VZV), cytomegalovirus (CMV), and adenovirus require arginine to replicate [ 13 16 ]. In vitro studies have demonstrated a decrease in HSV 1-2 replication, cell-to-cell transmission, and virus-mediated cytopathic effects in mediums deficient in L-arginine [ 13 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…L-Arginine also serves as an essential role in viral replication. Herpes simplex viruses (HSV-1 and HSV-2), varicella-zoster virus (VZV), cytomegalovirus (CMV), and adenovirus require arginine to replicate [ 13 16 ]. In vitro studies have demonstrated a decrease in HSV 1-2 replication, cell-to-cell transmission, and virus-mediated cytopathic effects in mediums deficient in L-arginine [ 13 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, l -arginine also serves an essential role in viral replication. Herpes simplex viruses (HSV-1 and HSV-2), varicella-zoster virus (VZV), cytomegalovirus (CMV), and adenovirus require arginine to replicate 2, 3, 4, 5. One in vitro study demonstrated suppression of HSV replication within cells lacking arginine, a phenomenon which was rapidly reversed with the introduction of l -arginine 2 …”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiments have shown arginine to be associated with the replication and virulence of a variety of viruses, including viruses from the herpes family 2, 3, 4, 5. These viruses are dependent on arginine-associated metabolic pathways in order to facilitate viral replication.…”
Section: Introductionmentioning
confidence: 99%
“…As such, peg-arginase 1 extends the survival of mice undergoing bone marrow transplantation and delays the appearance of graft versus host diseases, whereas enhancing the growth of Listeria ( 97 , 161 ). Additionally, peg-arginase 1 exerts a potent anti-herpetic activity, blocking herpes simplex virus replication and virus-derived cytopathic effects in vitro ( 162 ). Arginine-catabolizing enzymes have a preclinical additive and/or synergistic effects with other treatments such as chemotherapy, radiotherapy, PI3K inhibitors, and autophagy regulators ( 149 ), and the clinical efficacy of these combinatorial approaches remains to be determined.…”
Section: Therapeutic Implications and Concluding Remarksmentioning
confidence: 99%